Dissolved Oxygen and Apparent Oxygen Utilization in Lembeh Strait Waters, North Sulawesi - Patty, Simon I (Sam Ratulangi University, 2018)
The observation of dissolved oxygen level and Apparent Oxygen Utilization (AOU) in Lembeh Strait Waters was conducted in January, February, June and July 2016. The objective of this research is to know the condition of dissolved oxygen and Apparent Oxygen Utilization (AOU). The results of the analysis showed that dissolved oxygen levels in the surface layer and near the bottom ranged from 6.00-6.56 mg/l and 5.59-6.17 mg/l. Based on the values of temperature and salinity obtained from this study, solubility, oxygen saturation degree and AOU value at the surface layer were calculated. In the surface layer the AOU values are positive, ranging from 0.10-0.72 mg/l, while near the bottom, negative and positive AOU values were balanced, ranging from -0.23-0.42 mg/l. The concentration of dissolved oxygen in the Lembeh Strait waters has not shown negative impact on the aquatic environment and is still in accordance with sea water quality standards for marine biota.Keywords: Dissolved oxygen, apparent oxygen utilization (AOU), Lembeh Strait. ABSTRAK Pengamatan kadar oksigen terlarut dan Apparent Oxygen Utilization (AOU) di Perairan Selat Lembeh dilaksanakan pada bulan Januari, Februari, Juni dan Juli 2016. Penelitian ini bertujuan untuk mengetahui kondisi oksigen terlarut dan Apparent Oxygen Utilization (AOU). Hasil analisa menunjukkan bahwa kadar oksigen terlarut di lapisan permukaan dan dekat dasar berkisar antara 6,00-6,56 mg/l dan 5,59-6,17 mg/l. Berdasarkan nilai suhu dan salinitas yang diperoleh dari penelitian ini telah dihitung daya larut, derajat kejenuhan oksigen dan nilai AOU pada lapisan permukaan. Di lapisan permukaan nilai AOU semuanya positip berkisar antara 0,10-0,72 mg/l dan di dekat dasar nilai AOU negatip dan positip berimbang, berkisar antara -0,23-0,42 mg/l. Konsentrasi oksigen terlarut di perairan Selat Lembeh belum menunjukkan dampak negatip terhadap lingkungan perairan dan masih sesuai dengan baku mutu air laut untuk biota laut. Kata Kunci: Oksigen terlarut, apparent oxygen utilization (AOU), Selat Lembeh.